To Evaluate the Role of HbA1C as a Predictor for the Development of Diabetic Nephropathy in Type 1 Diabetic Patients (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: type 1 diabetic; diabeti c nephropathy; glycosylated hemoglobin (HbA1C)